Loss of Mpdz impairs ependymal cell integrity leading to perinatal‐onset hydrocephalus in mice - Feldner, Anja; Tetzlaff, Fabian; Komljenovic, Dorde; Sahm, Felix; Bäuerle, Tobias; Schroten, Horst; Korff, Thomas; Hofmann, Ilse; Deimling, Andreas von; Fischer, Andreas (EMBO molecular medicine, 2017)
Hydrocephalus is a common congenital anomaly. LCAM1 and MPDZ (MUPP1) are the only known human gene loci associated with non‐syndromic hydrocephalus. To investigate functions of the tight junction‐associated protein Mpdz, we generated mouse models. Global Mpdz gene deletion or conditional inactivation in Nestin‐positive cells led to formation of supratentorial hydrocephalus in the early postnatal period. Blood vessels, epithelial cells of the choroid plexus, and cilia on ependymal cells, which line the ventricular system, remained morphologically intact in Mpdz‐deficient brains. However, flow of cerebrospinal fluid through the cerebral aqueduct was blocked from postnatal day 3 onward. Silencing of Mpdz expression in cultured epithelial cells impaired barrier integrity, and loss of Mpdz in astrocytes increased RhoA activity. In Mpdz‐deficient mice, ependymal cells had morphologically normal tight junctions, but expression of the interacting planar cell polarity protein Pals1 was diminished and barrier integrity got progressively lost. Ependymal denudation was accompanied by reactive astrogliosis leading to aqueductal stenosis. This work provides a relevant hydrocephalus mouse model and demonstrates that Mpdz is essential to maintain integrity of the ependyma.